Changes in the expression of HLA-DR on lymphocyte subpopulations of spouses having children with sporadic congenital heart defects without chromosomal diseases, under the influence of female’s autoserum - A. V. Shabaldin; S. V. Grivtsova; N. S. Deeva; S. A. Shmulevich; A. V. Tsepokina; A. A. Anikeenko; E. V. Shabaldina; G. V. Vavin (Медицинская иммунология, 2021)
This study is aimed to investigate the effect of female autoserum on the HLA-DR expression in various subpopulations of lymphocytes obtained from spouses with children with sporadic congenital heart defects without chromosomal diseases. 78 married couples with children with congenital heart disease were included in the study group. The control group was formed from 35 married couples with healthy children. The immune response in a mixed culture of lymphocytes of spouses was evaluated by an increased HLA-DR expression in a mixed culture in relation to spontaneous cultures of lymphocytes. Primary staining of female and male lymphocytes by monoclonal antibodies to CD45 conjugated with various fluorescent dyes (PC-5 and PC-7) was performed to assess the immune response of female lymphocytes to male ones and vice versa. The activating effect of female autoserum on all subpopulations of female lymphocytes simultaneously occurred significantly less frequently in the study group compared to the control. The control group was characterized by the domination of the positive effect of female autoserum on HLA-DR expression for all subpopulations of female lymphocyte. For all female lymphocytes having HLA-DR molecule on its membrane, the blocking effect of female autoserum in the study group was significantly more expressed in relation to the control group. Thus, the effect of female autoserum is manifested in relation to the HLA-DR expression on its own lymphocytes, but not on the lymphocytes of the spouse.